Naravni parki in naravne znamenitosti v zgornjem toku rek Kolorado, Green River in San Juan - Kunaver, Jurij (Geografski obzornik, 2002)
The article deals with some of the most famous natural monuments in Southeast Utah and its direct vicinity, such as canyon-lands, natural arches, natural bridges, and results of erosion and solution, such as mesas and buttes. Some of these landscapes, for example the Monument Valley, have been host areas for moviemakers for several times. The Colorado plateau abounds in volcanic phenomena, too, such as isolated volcanic necks.
Keywords: Kolorado; naravna dediščina; naravne znamenitosti; naravni parki; Utah; varstvo narave; zaščita